PUNS AND TRANSLATION CHALLENGES: ΜΟΙΡΑΙΟΙ ΑΝΤΙΚΑΤΟΠΤΡΙΣΜΟΙ BY PETROS MARTINIDIS IN FRENCH AND IN ITALIAN (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
The present work proposes a comparative analysis of the French and Italian translations of puns extracted from the novel Μοιραίοι Αντικατοπτρισμοί (Reflections of Fate) by Petros Martinidis. Given the fact that the chosen Greek novel has been translated only into French, by Henri Tonnet, we tried to propose some Italian translation solutions of the analyzed passages. Therefore, word games based on sound (paronyms and homophones, homeoteleuton and alliterations) and on meaning (metaphors and figurative images, sayings and proverbs, amphibologies, and fixed expressions) are studied, as well as their translation from the source to the target language. Keywords: traductology; translation; puns; modern Greek literature; detective novel; Petros Martinidis.